2003
DOI: 10.1080/15330150390256782
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity Contests': Indigenously Informed and Transformed Environmental Education

Abstract: The 'biodiversity contest' is an educational innovation designed to uncover the plant diversity knowledge of children. This article, based on the experiences of the winners of 31 such contests, seeks to identify the methods through which children learn from their elders and the beliefs that the elders communicate to them. While elders develop in children knowledge about plants, they do not communicate a belief in active conservation. Though elders have a culturally determined preference for boys as apprentices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 5 publications
3
18
0
2
Order By: Relevance
“…Five of these (interest towards plants, identification of plants, harvesting of plants, processing for making final herbal products, and knowledge of rare plants), are foundational skills and were given more importance by established healers than other skills. This research supports findings of earlier studies and reiterates the importance of foundational skills of identification and harvesting of medicinal plants (Chand & Shukla 2003, Lozada et al 2006, Zarger 2000. The skills of application and consultation were considered as important TMK skills in an earlier study by Haarumaya (2003a).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Five of these (interest towards plants, identification of plants, harvesting of plants, processing for making final herbal products, and knowledge of rare plants), are foundational skills and were given more importance by established healers than other skills. This research supports findings of earlier studies and reiterates the importance of foundational skills of identification and harvesting of medicinal plants (Chand & Shukla 2003, Lozada et al 2006, Zarger 2000. The skills of application and consultation were considered as important TMK skills in an earlier study by Haarumaya (2003a).…”
Section: Discussionsupporting
confidence: 90%
“…These methods correspond generally with the eight-stage learning sequence model presented by Ruddle and Chesterfield (1977), where the learner moves from familiarization (developing interest about plants) to equal partner with instructors (assistance in actual practice and self-practicing). An earlier study by Chand and Shukla (2003) also confirmed that the choice of methods by elder Indian healers depended on the nature of skill to be taught and gender of learners. This gendered nature of TMK transmission highlights a direction for further research, namely, to examine the relationships between the choice of learning methods and the gender of learners in other forms of TEK knowledge, such as subsistence skills.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…This condition is affected by weak of awareness from young generation about traditional values. It also caused by high impact of modernization with lack guidance from elders [30,31]. Over all, total score of internal factors is 4.107 which in strong level (Table 3).…”
Section: Conservation Strategy Of Lowland Nepenthesmentioning
confidence: 99%